Pengaruh Literasi Keuangan, Persepsi Kegunaan dan Kemudahan terhadap Minat Menggunakan QRIS pada Pelaku UMKM di DKI Jakarta - Fardani, Fayza Eka; R Sudiarditha, I Ketut; Sebayang, Karuniana Dianta Arfiando (Jurnal Serambi Ekonomi dan Bisnis, 2024)
This study aims to determine the effect of financial literacy, perceived usefulness and easy of use on interest in using QRIS on MSMEs in DKI Jakarta. The method used in this research is quantitative. Data collection was carried out using purposive sampling technique. The data used is primary data obtained from distributing questionnaires. The population in this study are MSME players who are registered as members of JakPreneur and use QRIS as a means of payment. The sample in this study amounted to 100 respondents. The data analysis technique used is multiple linear regression analysis with the help of SPSS software version 22. The results of this study indicate that: (1) financial literacy has a positive and significant effect on interest in using QRIS, (2) perceived usefulness has a positive and significant effect on interest in using QRIS, (3) perceived easy of use has a positive and significant effect on interest in using QRIS, (4) financial literacy, perceived usefulness, and perceived easy of use simultaneously have a positive and significant effect on interest in using QRIS.